Sinkretisme Islam dan Hindu (Studi Terhadap Tradisi Rasol Bu’sobu’ Pelet Betheng di Desa Gunung Sekar Madura) (Journal of Comparative Study of Religions, 2024)
Tradition and culture give another color to the living conditions of the community. The traditions and cultures adopted provide an explanation of religious practices. Although in essence culture is the result of human creation that has certain norms and rules. Rasol Bu’sobu’ pelet Betheng tradition, for example, is one of the traditions in Java, intended for pregnant women whose pregnancies have entered the seventh month. In this tradition there is a mixture of Islamic and Hindu elements. The ritual begins with reading verses from the Qur'an and from Surah Yusuf, Surah Maryam and prayers to the Prophet with the hope that the newborn baby will make the Qur'an and Hadith the source of his life. These are the elements that exist in Islam. Hindu elements include giving food to gods and goddesses or to spirits known from supernatural whispers. Bathing to purify the body and soul from mistakes or sins, as well as bringing seven flowers, eggs, young coconuts, and a chicken.